Tarkīb al-Ījāz dan al-Iṭnāb: Kajian dan Fungsinya dalam Penafsiran Al-Qur’an - Riyadh Al-Shalihin, Muhammad; Harjum, Mohamad; Abdullah, Dudung (Dirosah Islamiyah, 2026)
The Qur'an is the greatest miracle of Prophet Muhammad (PBUH), possessing linguistic beauty and depth of meaning that cannot be rivaled by humans. One aspect of the Qur'an's linguistic miraculousness is evident in its use of effective and communicative stylistic devices, specifically the concepts of ījāz (conciseness) and iṭnāb (elaboration) within the science of balāghah (Arabic rhetoric). Ījāz is a stylistic approach that conveys meaning succinctly without compromising the clarity of the message, whereas iṭnāb conveys meaning through more extensive exposition for the purposes of emphasis, clarification, or reinforcement. This study aims to explain the concepts of ījāz and iṭnāb, their various types, and their functions and applications within the Qur'an. It employs a library research methodology with a qualitative approach. Data were gathered from the Qur'an, classical balāghah texts, works on Ulūm al-Qur'ān (Qur'anic sciences), and scholarly journals discussing ījāz and iṭnāb. A descriptive-analytical method was used to examine the theories of balāghah scholars alongside examples of their application in Qur'anic verses. The findings indicate that ījāz and iṭnāb are complementary stylistic devices that contribute to the beauty and miraculous nature of the Qur'an. Ījāz ensures effective communication through expressions that are brief, compact, and rich in meaning, while iṭnāb reinforces the message by providing explanations, emphasis, or details as required by the context. The use of these two styles demonstrates that every sentence structure in the Qur'an serves a precise rhetorical purpose, enabling the message to be conveyed beautifully, accurately, and profoundly. Consequently, an understanding of ījāz and iṭnāb is essential to the study of balāghah for a more comprehensive grasp of the linguistic miraculousness of the Qur'an.